Deutsche Musik in der Prime Time des Radios - Einenkel, Maxi; Fecho, Susanne; Scholz, Nina; Justus Liebig University Giessen (My University, 2014)
Over 80% of the German population listen to the radio every day. For them the music is more important than the news broadcast. The authors of this paper wanted to know under what aspects the music program in German radio is planned. Therefore two mainstream radio stations in Hessen, hr3 and Hit Radio FFH, were chosen to evaluate the playlists of their prime time morning show over a period of several weeks. Afterwards the authors led interviews with the head of FFH and the music director of hr3. This research focuses on the question to what extend German radio plays German or rather German-speaking music and if there are differences between private and public-serving broadcasting. Furthermore it questions the stations´ attitudes towards a legal radio quota agreement of German music.
Keywords: ddc:780